Hubungan Tingkat Kepatuhan Petani Hortikultura Dataran Rendah dalam Penggunaan Pestisida terhadap Populasi Hama, Penyakit, Musuh Alami, dan Keamanan Produk - SHK, Suparman; Irsan, Chandra; Margaretha, Shera (Politeknik Negeri Lampung, 2024)
The improper use of pesticides can lead to significant negative impacts on both the environment and human health. This study evaluates horticultural farmers' compliance with recommended pesticide practices in Ogan Ilir Regency, South Sumatra, and examines the effects on pests, diseases, natural enemies, and pesticide residues in their products. This research used a direct survey method on horticultural crop cultivation land in Ogan Ilir Regency, South Sumatra, and sent plant samples to be tested for pesticide residue levels. The results showed that low-compliance farmers had high pest populations, high disease incidence, and fewer natural enemies, while high-compliance farmers had low pest populations, low disease incidence, and more natural enemies. Pesticide residue tests indicated that products from low-compliance farmers contained Amitraz residues of 0.02 mg/kg and Chlorantraniliprole residues of 0.14 mg/kg, while medium-compliance farmers had Amitraz residues of 0.02 mg/kg and Chlorantraniliprole residues of 0.18 mg/kg. No pesticide residues were detected in products from high-compliance farmers. The study concludes that adherence to recommended pesticide use significantly influences the balance of agricultural ecosystems and the safety of agricultural products.